MONITORING OF EFFECTIVENESS OF SPIRONOLACTONE THERAPY AND ITS COMBINATIONS WITH FUROSEMIDE TO LIVER CIRRHOSIS AND ASCITES IN RSUP H. ADAM MALIK MEDAN - Siswanti, Elliya; Harahap, Urip; Sembiring, Juwita (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: Spironolactone and furosemide are diuretics used to treat liver cirrhosis with ascites, but not case studies have been found to distinguish the effects of spironolactone and its combination with furosemide in cases of cirrhosis accompanied by ascites. This study aims to determine the effectiveness of spironolactone therapy and its combination with furosemide to liver cirrhosis patients accompanied ascites. Methods: This research was done by cross-sectional prospective method. 26 patients in RSUP H Adam Malik Medan for 3 months were divided into two groups. The first group of nine patients, age between 39 and 65 years, was given spironolactone. The second group of 17 patients, age between 20 and 81 years, was given spironolactone combined with furosemide. The sample data were analyzed with statistics using Mann–Whitney U-test, SPSS program version 22. Result: Based on Mann–Whitney U statistic test, the value of Asymp. significance (2-tailed) 0.435 for urine Na/K at time, and Asymp. significance value (2-tailed) 0.628 24 h urine sodium examination, based on the value, it was concluded that there was no significant difference between spironolactone with its combination with furosemide. Even though the significant value were 0.628 mEq and 0.435 mEq (p>0.05). Conclusion: This study showed that the combination of spironolactone with furosemide was better than compared to spironolactone. Although there was not statistically significant difference if seen from the comparison of 24 h of urine sodium value with a normal value of 78 mEq.